Modeling and Simulation in an Educational Context: Teaching and Learning Sciences - Carlos Jorge Brigas (Research in Social Sciences and Technology- OpenED Network, 2019)
In science education, there is a need to evaluate the behavior of dynamic systems. Representing and explaining processes through educational models or simulations enables students to perform activities where it is easier to understand these processes and discover the essential properties of a system. Performing modeling or simulation activities that promote interpretation and understanding of systems are learning activities in which students have the ability to create and test their own perceptions of a given phenomenon. Although such activities enhance the development of skills such as reflection, decision making, creativity and generalization, the use of these activities in educational contexts is very sporadic. The difficulties teachers experience in using this type of activity relate to the types of models that are usually used to represent a system, the specificities needed to represent them, the degree of complexity of modeling and simulation tools to do so, and the lack of preparedness to implement practical research activities. In this research, we present the Modeling for Kids methodology to support the development of georeferenced multisensory modeling and simulation activities for the first cycle of Basic Education. This methodology lists a set of norms that aim to advise the teacher and the student in the accomplishment of these activities. The methodology identifies the strategies, contexts of use, and curriculum areas where these activities can be inserted. It also identifies the processes of analysis and representation of dynamic systems. Due to the importance and advantages of georeferenced multisensory information in learning, the methodology also prescribes that teachers and students use this type of information in modeling and simulation activities.